Mekanisme Self Report Perpres No. 57 Tahun 2023 dengan Kewajiban Negara Memenuhi Hak Bekerja - Irgiansyah, Krisna; Sella Rahma Maulida; Freidelino P. R. A. de Sousa (Jurnal Ilmiah Penegakan Hukum, 2024)
The objective of this article is to examine the relationship between the right of citizens to employment and the state's obligation to fulfil that right. In this context, it is necessary to consider the role of the state as an active agent in ensuring the realisation of this right. Furthermore, it seeks to justify the incompatibility of implementing the self-report mechanism in relation to the state's obligation to fulfil citizens' right to employment. The issue can be defined as a conceptual inaccuracy in the implementation of a theoretical framework for the fulfilment of human rights. This theoretical framework should, in theory, oblige the state to fulfil the rights of every citizen as set out in the constitution. Nevertheless, the state appears to be abdicating its responsibilities by delegating them to employers. This article employs a normative juridical approach with a statutory methodology. Data are collected through literature studies that are pertinent and current, and which inform the qualitative analysis of the material to be reviewed. This study finds that the self-report mechanism set forth in Article 4, paragraph (2) of Presidential Regulation No. 57 of 2023 is incompatible with the state's obligation to fulfill the right to work. This is because the mechanism makes the state passive in carrying out its obligations. It is incumbent upon the government to take proactive measures to fulfil its obligations regarding citizens' rights to employment, as enshrined in Article 27, paragraph (2) of the 1945 Constitution and Article 38, paragraph (1) of Law No. 39 of 1999.